The full-information best-choice problem with uniform or gamma horizons. (2nd April 2016) - Bendersky, Michael; David, Israel
Abstract : A decision-maker has to choose one from among a Poisson stream of i.i.d. bids, with no recall. The stream stops at a random time with a uniform (in the first case) or Erlang (in the second case) distribution. We solve the problem explicitly for maximal expected gain for bids that may take on any finite number of values. A fast procedure to solve the problem for fixed horizon is presented as well.